Pharmacokinetics of rituximab and clinical outcomes in patients with anti-neutrophil cytoplasmic antibody associated vasculitis. (10th January 2018) - Cornec, Divi; Kabat, Brian F; Mills, John R; Cheu, Melissa; Hummel, Amber M; Schroeder, Darrell R; Cascino, Matthew D; Brunetta, Paul; Murray, David L; Snyder, Melissa R; Fervenza, Fernando; Hoffman, Gary S; et al.
Abstract: Objectives: To study the determinants of the pharmacokinetics (PK) of rituximab (RTX) in patients with ANCA-associated vasculitis (AAV) and its association with clinical outcomes. Methods: This study included data from 89 patients from the RTX in AAV trial who received the full dose of RTX (four weekly infusions of 375 mg/m 2 ). RTX was quantified at weeks 2, 4, 8, 16 and 24, and summarized by computing the trapezoidal area under the curve. We explored potential determinants of the PK-RTX, and analysed its association with clinical outcomes: achievement of remission at 6 months, duration of B-cell depletion and time to relapse in patients who achieved complete remission. Results: RTX serum levels were significantly lower in males and in newly diagnosed patients, and negatively correlated with body surface area, baseline B-cell count and degree of disease activity. In multivariate analyses, the main determinants of PK-RTX were sex and new diagnosis. Patients reaching complete remission at month 6 had similar RTX levels compared with patients who did not reach complete remission. Patients with higher RTX levels generally experienced longer B-cell depletion than patients with lower levels, but RTX levels at the different time points and area under the curve were not associated with time to relapse. Conclusion: Despite the body-surface-area-based dosing protocol, PK-RTX is highly variable among patients with AAV, its main determinants being sex and newly diagnosed disease. We did not observe any relevant association between PK-RTX and clinical outcomes. The monitoring of serum RTX levels does not seem clinically useful in AAV.